PENGARUH WORK OF MOUTH, PERCEIVED VALUE DAN SWITCHING COST TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE - Hermawan, M Rafly; Arianto, Tezar (UM. Bengkulu, 2025)
This study aims to determine the influence of word of mouth, perceived value and switching cost, on smartphone purchase decisions in students of the University of Muhammadiyah Bengkulu Management Study Program. This type of research is a descriptive quantitative approach with the sample of this research is 259 respondents from the University of Muhammadiyah Bengkulu management study program. The data collection techniques in this study are observations and questionnaires measured using the Likert scale. The data analysis techniques used were multiple linear regression, determination coefficient, and hypothesis test. The independent variable affects the dependent variable. Word of mouth, switching cost and perceived value together show the influence on smartphone purchase decisions on students of the University of Muhammadiyah Bengkulu management study program. Keywords : Word of Mouth, Switching Cost, Perceived Value, Purchase Decision